Diretrizes para licitações de projetos de sistemas prediais de água fria e esgoto sanitário em campi universitários - Cover, Marcelo Pinarelli (2012)
In the context of the plumbing systems, the design stage may be responsable for considerable parcel of pathological manifestations that may occur after the building occupation. These problems can bring negative impact for the users, considering the built environment, and also demands premature maintenance with respective extra costs, which may decrease the building lifetime. In this context, this dissertation aims to propose guidelines that can be used in the bidding for projects of building systems of cold water and sanitary sewer in university campuses. The method used for the research was the case study. Firstable, a bibliographic survey was carried out by addressing the systems studied, the concepts of performance evaluations, as well as a collection of studies on pathologies, that had served to appraise the work. The guidelines, final result of this research, was developed, based on a survey of criteria and performance requirements present in the NBR 15575: 2008 Residential buildings of up to five floors Performance (ABNT, 2008), and based else in the author experience in the area. After that, two projetcs on Campus Are Carlos from the Federal University of São Carlos were analysed, as practice demonstration of the obtained results.